Lung Pericytes and Resident Fibroblasts: Busy Multitaskers - Barron, Luke (Am J Pathol, 2016)
Pericytes, resident fibroblasts, and mesenchymal stem cells are poorly described cell populations. They have recently been characterized in much greater detail in rodent lungs and have been shown to play important roles in development, homeostasis, response to injury and pathogens, as well as recovery from damage. These closely related mesenchymal cell populations form extensive connections to the lung's internal structure, as well as its internal and external surfaces. They generate and remodel extracellular matrix, coregulate the vasculature, help maintain and restore the epithelium, and act as sentries for the immune system. In this review, we revisit these functions in light of significant advances in characterizing and tracking lung fibroblast populations in rodents. Lineage tracing experiments have mapped the heritage, identified functions that discriminate lung pericytes from resident fibroblasts, identified a subset of mesenchymal stem cells, and shown these populations to be the predominant progenitors of pathological fibroblasts and myofibroblasts in lung diseases. These findings point to the importance of resident lung mesenchymal populations as therapeutic targets in acute lung injury as well as fibrotic and degenerative diseases. Far from being passive and quiescent, pericytes and resident fibroblasts are busily sensing and responding, through diverse mechanisms, to changes in lung health and function.